PEDAGOGICAL USE OF REPETITION IN DEVELOPING SPEAKING SKILLS - Rasulova Muborak (PEDAGOGS, 2025)
Annotation: Repetition plays a vital role in the development of learners’ speaking competence, particularly in foreign language teaching. The pedagogical use of repetition is not merely a mechanical activity but a cognitive and communicative process that enhances fluency, accuracy, and pronunciation. Through repeated exposure and production, students internalize linguistic patterns, develop automaticity, and gain confidence in spontaneous speech. This paper discusses the theoretical foundations of repetition from psycholinguistic and communicative perspectives, emphasizing its role in habit formation, memory consolidation, and communicative competence.